Identifying Fetal Alcohol Spectrum Disorder and psychiatric comorbidity for children and youth in care: A community approach to diagnosis and treatment. (January 2020) - Patel, Mitesh; Agnihotri, Sabrina; Hawkins, Connor; Levin, Leo; Goodman, Deborah; Simpson, Alexander
Highlights: Limited research exists on the diagnosis of Fetal Alcohol Spectrum Disorder (FASD) for children and youth in care. These youth are at increased risk for developing comorbid mental health conditions. This study describes an assessment service for youth in care suspected of a diagnosis of FASD and then referred for general psychiatric assessment. The majority of youth who were initially screened by their child protection worker using a validated tool were determined to have met criteria. Psychiatric comorbidity was diagnosed and treatment recommendations made for all children and youth referred. We encourage that youth in care be screened for FASD using an integrated approach to facilitate more timely diagnosis and early intervention. Abstract: Background: Several challenges exist when making a diagnosis of Fetal Alcohol Spectrum Disorder (FASD) and identifying co-morbid psychiatric illness, particularly for children and youth accessing child welfare services. Here, we describe an integrated three-phase approach to the identification of FASD and psychiatric comorbidity for children and youth in care, consisting of: (1) completion of a standardized neurobehavioral screening tool by a child protection worker (CPW); (2) assessment by a pediatrician, including facial measurements and; (3) integration of findings in a psychiatric assessment. Main Findings: The majority of participants (14/18, 78%) of youth who were suspected by a CPW and pediatrician of a diagnosis of FASD using the screening tool were determined to have met criteria. A diagnosis was made in all cases where there was confirmed history of prenatal exposure and a majority of these youth were found to have sentinel facial features of FASD. Psychiatric comorbidity was diagnosed and treatment recommendations made for all children and youth referred. Conclusions: This study supports the utility of an integrated community approach to diagnosing and treating comorbid psychiatric disorders in FASD by employing existing child protection and physician services in a community setting. Based on these preliminary findings, we encourage that youth who access formal care systems be screened for FASD by their CPW and are provided with appropriate pediatric and psychiatric assessments to clarify the diagnosis, while also identifying comorbid psychiatric illness to target appropriate interventions.